Defining a Novel Meaning of the New Organic Architecture - Jia-Rey Chang (A+BE: Architecture and the Built Environment)
Starting an overall investigation by categorizing current bio-inspired architectural design developments into “Material”, “Morphological”, and “Behavioral” to explore a novel definition of the “New Generation Organic Architecture”.